Prognostic indicators for mast cell tumors - Strefezzi , Ricardo F.; Kleeb, Silvia R.; Xavier , José G.; Catão-Dias, José L. (Brazilian Journal of Veterinary Pathology, 2009)
Mast cell tumors are among the most common canine cutaneous neoplasms. These tumors are routinely graded with regard to malignancy based on histomorphological features which are related to the post-surgical course of the disease. This classification is the main criterion for clinicians and surgeons to direct the therapy. However, mast cell tumors biologic behavior is extremely variable, leading to frequent failure in treatment. This occurs, for the most part, in tumors with moderate differentiation and can be explained by the fact that they share histomorphological features with the well- differentiated and the poorly-differentiated tumors. Because of these difficulties, several methods have been studied with the objective of predicting tumor behavior and the evolution of the cases in a more precise and trustful manner. The present work reviews the main aspects of this important neoplasm, as well as the available literature about the prognostic indicators, commenting their advantages, disadvantages and the results obtained by various authors.